Teaching and learning the sciences in Islamicate societies (800-1700) - Brentjes, Sonja 1951- (Studies on the faculty of arts, 2018)
This book surveys teaching and learning of the mathematical and occult sciences, medicine and natural philosophy in various Islamicate societies between 800 and 1700. It focuses in particular on Egypt and Syria between 1200 and 1600, but looks up also developments in Iran, India, Anatolia, and Iraq. It talks about institutions of teaching and learning such a house and court teachers, madrasas, hospitals, in-family teaching and travelling in search of knowledge and the content of the various sciences taught by or at them. Methods of teaching and learning, teaching bestsellers and their geographical and temporal dissemination, as well as encyclopaedias and literature on the classification of the sciences will be discussed in further chapters